A review of Neotropical species in Thienemanniella Kieffer (Diptera, Chironomidae) - Wiedenbrug, Sofia; Lamas, Carlos E.; Trivinho-Strixino, Susana (Zootaxa, 2013)
Three species previously described from the neotropical region are revised and four new species are described: Thienemanniellabiobio sp. n. and T. manihuales sp. n. as males and pupae from Chile, T. sancticaroli sp. n. and T. ubatuba sp.n. as males, females and immature stages from Brazil. The new Thienemanniella spreta species group is delimited consistingof T. spreta (Roback) sensu Sublette & Sasa, T. sanctivincenta Saether, T. liae Paggi, T. sancticaroli sp. n. and T.ubatuba sp. n. Keys to the known Neotropical males, pupae and larvae are presented.